Functionalizing graphene oxide framework membranes with sulfonic acid groups for superior aqueous mixture separation. Issue 34 (16th August 2019) - Yang, Guang; Xie, Zongli; Cran, Marlene; Ng, Derrick; Easton, Christopher D.; Ding, Mingmei; Xu, Hang; Gray, Stephen
Abstract : Hydrophilic pervaporation (PV) membranes with ultrahigh throughput and outstanding separation ability are highly beneficial for efficient separation of aqueous mixtures. Abstract : Hydrophilic pervaporation (PV) membranes with ultrahigh throughput and outstanding separation ability are highly beneficial for efficient separation of aqueous mixtures. However, it is still challenging to obtain high selectivity without compromising water permeation flux for state-of-the-art PV membranes. Herein, a sulfosuccinic acid (SSA) covalently linked graphene oxide (GO) membrane is developed via a facile vacuum filtration process on a nylon substrate followed by heat treatment. During the membrane fabrication process, ester groups form through the dehydration condensation reaction between –COOH from the SSA and –OH from the GO. The resultant graphene oxide framework (GOF), with well-defined two dimensional nanocapillaries functionalised by unreacted –SO3 H, features enhanced hydrophilicity and remarkable swelling resistance, leading to excellent separation performance with ultrahigh water permeation fluxes and precise molecular sieving properties towards both dehydration of alcohol and desalination. This research provides a strategy to dramatically enhance the performance by adding unreacted, additional functional groups into the GOF membranes.